CORPORATE SOCIAL RESPONSIBILITY PROJECTS FOR EDUCATION IN TURKEY WITHIN THE CONTEXT OF RELATIONSHIP BETWEEN PRIVATE SECTOR AND NGOs - Bicakci, Ilker (ISTANBUL UNIV, 2008)
This study handles the social responsibility concept which has become important as a result of minimal state policies, emerged after social welfare state. The state, which has lost its protectionist and inclusive characteristic over public sphere, has remained useless in satisfying basic human rights such as health or education paradoxically, while continuing with its taxation function. The responsibility area of the social welfare state has become smaller together with the globalization. Besides, these fields in which enormous gaps of service exist have offered new profit opportunities to companies through privatization. Health and education services carried on by present public bodies are becoming more and more dependent on money. Class inequalities are more common in the countries like Turkey. Therefore, education stands out as the basic social welfare fields. The private sector who adopts corporate social responsibility is conducting various projects collaborating with Non governmental Organizations (NGOs). In this study, a descriptive analysis based on the corporate web sites of various NGO's, is performed with a critical perspective. As a result, rather than their limited contribution to the social life, social responsibility projects in the field of education bring added value to the private sector as an output of corporate public relations.
Keywords: Corporate social responsibility; education; NGOs; Communication